(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
The study of teaching the subject “Upbringing” in primary grades as a pedagogical problem reveals the complex, multifactorial, and dynamic nature of the educational process. At this stage, a child’s moral and ethical development, social adaptation, emotional experience, and communicative competencies begin to take shape. The effectiveness of upbringing depends on the teacher’s methodological approach, psychological sensitivity, cooperation between family and school, and the ability to adapt to the demands of the modern social environment.